Studies of inclusive four-jet production with two b-tagged jets in proton-proton collisions at 7 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Ero, J.; Flechl, M.; Friedl, M.; et al. (My University, 2016)
Measurements are presented of the cross section for the production of at least four jets, of which at least two originate from b quarks, in proton-proton collisions. Data collected with the CMS detector at the LHC at a center-of-mass energy of 7 TeV are used, corresponding to an integrated luminosity of 3 pb(-1). The cross section is measured as a function of the jet transverse momentum for p(T) > 20 GeV, and of the jet pseudorapidity for |eta| < 2.4 (b jets), 4.7 (untagged jets). The correlations in azimuthal angle and pT between the jets are also studied. The inclusive cross section is measured to be sigma(pp -> 2b + 2j + X) = 69 +/- 3(stat) +/- 24(syst) nb. The eta and p(T) distributions of the four jets and the correlations between them are well reproduced by event generators that combine perturbative QCD calculations at next-to-leading-order accuracy with contributions from parton showers and multiparton interactions.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Collaboration, C. M. S. (2016). Studies of inclusive four-jet production with two b-tagged jets in proton-proton collisions at 7 TeV. Physical Review D, 94(11), 24. doi:10.1103/PhysRevD.94.112005
Keywords: Astronomy & Astrophysics; Physics